Examination of the antioxidant effects of pre-HSG melatonin use on ovarian surface epithelium in rats: An experimental study - Yilmaz, Esra Saygili; Sapmaz, Tansel; Kazgan, Halil; Yildiz, Sule Menziletoglu; Kocamaz, Derya; Akpolat, Nusret; Sapmaz, Ekrem (Wroclaw Medical Univ, 2018)
Background.There is no study of whether the dysplastic changes in the ovarian surface epithelium of X-ray-exposed rats during hysterosalpingography (HSG) decrease or not with the use of Lipiodol and melatonin given both intiaperitoneally (i.p.) and into the suspensorium ovarii. Objectives. We investigated the restorative effects of melatonin and Lipiodol admimstiation during the HSG piocedure on the dysplastic changes in the ovarian surface epithelium of X-ray-exposed rats. Material and methods. A total of 50 Wistar rats with regular estrous cycles were randomly divided into 5 groups. Group 1 was the control group. In other groups, X-ray was applied (group 2), 0.1 mL Lipiodol was applied to each uterine horn (group 3),20 mg/kg intraperitoneal melatonin application was followed by 0.1 mL Lipiodol administration to each uterine horn after 15 min (group 4), and 20 mg/kg melatonin was administered to the ligamentum suspensorium ovarii, followed by 0.1 mL Lipiodol application to each uterine horn after 15 min (group 5). The rats in groups 2-5 were exposed to whole body radiation 3 times. After 3 h, the abdomens of all rats were reopened and left oophorectomy was performed. Results. The presence of nucleoli and mitosis values were found similar among the groups. All other palameters were significantly higher in group 2 compated to other groups, except for the presence of nucleoli and mitosis values (p < 0.05). The presence of hyperchromasia and the total score were found to be the highest in group 2, followed by group 3, when compared to other groups (p < 0.05). It was detected that the detrimental effects of X-iay exposure diminished with Lipiodol use, and were further reduced by the use of melatonin in combination. Conclusions. We suggest that the use of melatonin and Lipiodol during HSG may prevent the carcinogenic changes exeited by radiation on the ovarian suiface epithelium.
Keywords: melatonin; hysterosalpingography; rats; radiation; Lipiodol